The approval in the Ecuadorian Labor Procedural Law and its Influence on Labor Stability - Rivadeneira Rivadeneira , Eddie Fernando (2025)
The work had its genesis in the analysis of the administrative acts in relation to the application of the approval to terminate the labor relationship between employers and workers, the research was developed through techniques or information tools such as the descriptive and qualitative method which allowed the collection of a vast amount of reliable information. This made it possible to identify the deficiencies and limitations that exist on the part of the labor inspector in relation to notification and response times, which prevents the parties involved from being unable to present solid evidence to support their petition. The results were clear and precise in identifying the problem in relation to this administrative act, therefore, it is concluded that this should be known and dealt with by the corresponding specialized jurisdiction, guaranteeing respect for due process and legal certainty in the resolution of conflicts.